Targeting Aß oligomers: a molecular basis for the cause, diagnosis, and treatment of Alzheimer’s disease - Klein, William L. (Henry Stewart Talks, 2014)
The oligomer cascade hypothesis for Alzheimer’s Disease, why the oligomer hypothesis has largely supplanted the amyloid cascade hypothesis, the role of AβOs in memory failure and the major facets of AD neuropathology, mechanisms by which AβOs instigate neurotoxicity, why AβOs accumulate in the first place, how AβOs offer superb targets for novel AD diagnostics and disease-modifying therapeutics, beside its direct link to Alzheimer’s disease, the discovery of toxic Aβ oligomers has provided a novel structural archetype for toxins germane to more than two dozen diseases of protein mis-folding, including diabetes, Parkinson’s, and prion diseases